Emerging strategies to overcome ovarian cancer: advances in immunotherapy - Massariol Pimenta, Tatiana; Carlos de Souza, Josiany; da Silva Martins, Bárbara; Silva Butzene, Solenny Maria; Simões Padilha, José Matheus; Ganho Marçal, Milleny; dos Santos Elias, Guilherme; Rangel, Leticia Batista Azevedo (Frontiers in Pharmacology, 2024)
Ovarian cancer is the second most common malignant neoplasm of gynecological origin and the leading cause of death from cancer in the female reproductive system worldwide. This scenario is largely due to late diagnoses, often in advanced stages, and the development of chemoresistance by cancer cells. These challenges highlight the need for alternative treatments, with immunotherapy being a promising option. Cancer immunotherapy involves triggering an anti-tumor immune response and developing immunological memory to eliminate malignant cells, prevent recurrence, and inhibit metastasis. Some ongoing research investigate potentially immunological advancements in the field of cancer vaccines, immune checkpoint blockade, CAR-T cell, and other strategies.